Intravenous iloprost in the combination therapy of vascular disorders in patients with systemic connective tissue diseases - Aleksandr Vitalyevich Volkov; N N Yudkina (Современная ревматология)
Systemic connective tissue diseases, systemic scleroderma in particular, constitute a group of diseases in which vascular disorders underlying diverse clinical manifestations are one of the pathogenetic components. Raynaud 's syndrome and ulceration are the most common symptoms of these diseases, which influence quality of life in patients and require constant drug therapy. The paper discusses the authors' clinical experience with intravenous iloprost used in the combination therapy of the vascular manifestations of systemic scleroderma and systemic lupus erythematosus.